Creating courses for adults design for learning - St. Clair, Ralf (San Francisco, California Jossey-Bass, 2015)
"Provides a systematic approach to lesson and course design based on research into the ways adults learn and the best ways to reach them, along with pointers and tips for teaching adults in any setting"--Provided by publisher.
PART ONE Core Factors in Teaching : All About You; Why Who You Are and What You've Done Matters; Reflecting on Your Approach; What Are We Doing It For?; Why Identity Matters; Going Further; Conclusion: Pulling It Together -- Engaged and Involved Learners :How Do People Learn?; Engagement in Learning; Learner Diversity; Responding to Diversity; Conclusion: Making Difference Matter -- Context Drives Design : Why Context Matters; Ball Gown or Boots: Formality; Wired Learning; Organizational Context; The Aims of the Course; Time, or the Lack Thereof; Somewhere to Sit: Physical Resources; Conclusion -- The Key Decisions : Knowing Where You Are Going : Objectives and Some Objections; The Educator; The Learners; The Context; Conclusion; -- Content and Resources for Learning; Information and Objects; Resources and Materials; The Educator; The Learners; The Context; Conclusion -- Ways of Working Together; The Range of Methods; The Educator; The Learners; The Context; Conclusion -- What Do the Learners Say? : Designing Evaluation; The Educator; The Learners; The Context; Conclusion -- Making Learning Visible : Counting What Counts; The Educator; The Learners; The Context; Conclusion -- You Can Take It with You!; Moving Learning beyond the Course; The Educator; The Learners; The Context; Conclusion -- Design Frames Practice : The Book in a Box; An Example of a Program Design; For New Educators of Adults; Conclusion.
Includes bibliographical references (pages 193-198) and index.
Keywords: Adult education; Lesson planning